Psychosynthesis using Empathic Love Therapy (ELT) to reduce Depression and Anxiety Case Report on a group of Emerging Adults - Gandawijaya, Leonardus Edwin; Yuniarti, Kwartarini Wahyu (Gadjah Mada Journal of Professional Psychology (GamaJPP), 2025)
Depression and anxiety are strong indicators of difficulties in the process of recentering during emerging adulthood. Although various interventions exist to address these issues, group psychosynthesis offers efficient treatment in developing countries. This case report highlights the experiences of seven university students who participated in Empathic Love Therapy (ELT) group to reduce depression and anxiety, as measured by the Patient Health Questionnaire Anxiety and Depression (PHQ-ADS) scale (d = 1.79; p < .01). The application of psychosynthesis through the Empathic Love Therapy (ELT) module in a group setting demonstrates potential as a cost-effective option for primary healthcare professionals, particularly in addressing the rising number of students at risk of self-harm or suicide.